Improving Teacher Professionalism trough Lesson Study - Effendi, Muh Saeful (Ahmad Dahlan Journal of English Studies, 2015)
AbstractBeing professional teacher is a process of acting and reflecting continuously developed by the teachers collaboratively. Lesson Study facilitates teacher to experience learning through collaborative work among them. This enables teachers to establish professional development and create a community for learning. This paper aims at elaborating the experience of senior high school at Yogyakarta in implementing Lesson study as a break-through to enhance the teachersâ professional development incorporating with three mechanisms of Lesson Study. This school has conducted Lesson Study for about 5 years. The study resulted that 80 percent of teachers achieve their competence in planning, doing and reflecting the lesson through observing other teachers performance and being observed interchangeably.